Study guides

Q: How do you factor T2 plus 4T?

Write your answer...

Submit

Related questions

(u + 4)(6u - t)

(3t + 2)(4t - 1)

(t + 7)(t - 1)

(t - 7)(t - 11)

4t + 13t + 2 = 17t + 2

4(t + 3)(t2 - 3t + 9)

If 4t + 5 = 37, then t = 8.

4t2 - 12 = 4*(t2 - 3) which has no further rational factors

4t +7

math

There are no solutions because the discriminant of this quadratic equation is less than zero

9t = 4t + 120 9t-4t = 4t - 4t + 120 5t = 120 5t/5 = 120/5 t = 24 24 is your answer

Subtract 21 from both sides. If that's + 4t, the answer is (t - 3)(t + 7) and t = 3, -7 If that's - 4t, the answer is (t + 3)(t - 7) and t = -3, 7

4t - 2p

x2 is the same as x times x. In this case x = t+2 so we can say (t+2)2 is (t+2)(t+2) or t2+4t+4

-3t+5

T+(3-2t)=4t+1. Assuming the two T's , T and t are the same variable, lets proceed. t+(3-2t)=4t+1 3-t=4t+1 2-t=4t 2=5t last step is yours

7s + 4t

NEVERMIND!

t2 - 59t + 54 - 82t2 + 60t = - 81t2 + t + 54

That's one term. You need at last two to find an LCM. That factors to t(t + 2)(t + 2)

2

4t-1 = t+2 3t -1 = 2 3t = 3 t = 1

28 t2 - 17 t - 3 = (7t + 1) x (4t - 3)

It is an equation and the value of t is 1